Assessing 4C Competencies in English Language Learners: Tools, Challenges, and Implications - Anggraini, Yanti; Setiawati, Setiawati; Sari, Ika Purnama (The Study Program of English Education of Palangka Raya University, 2024)
In the era of globalization and the Fourth Industrial Revolution, 21st-century skills—Critical Thinking, Communication, Collaboration, and Creativity (4C)—are essential for learners' success in dynamic and competitive environments. This study evaluated 4C competencies in English language learners, focusing on comprehensive assessment tools, challenges, and implications. The literature review method was used to analyze various peer-reviewed sources, highlighting effective tools such as rubrics, performance-based assessments, and technology-enhanced platforms. Challenges include the subjective nature of evaluating creativity and the necessity for extensive teacher training. The study emphasized the need for integrating 4C skills into English language curricula to create dynamic learning environments that enhance both language proficiency and essential life skills. The findings suggested that adopting innovative assessment strategies and providing ongoing professional development for educators are crucial. Ultimately, assessing and cultivating 4C competencies will contribute to developing adaptable, innovative, and effective communicators, preparing students for the complexities of the 21st century. Continuous research and investment in this area are vital for advancing English language teaching and learning.